Viability and Contractility of Rat Brain Pericytes in Conditions That Mimic Stroke; an in vitro Study - Heyba, Mohammed; Al-Abdullah, Lulwa; Henkel, Andreas W.; Sayed, Zeinab; Malatiali, Slava A.; Redzic, Zoran B. (Frontiers in Neuroscience, 2019)
Reopening of the cerebral artery after occlusion often results in “no-reflow” that has been attributed to the death and contraction (rigor mortis) of pericytes. Since this hypothesis still needs to be confirmed, we explored the effects of oxygen glucose deprivation (OGD) on viability and cell death of primary rat pericytes, in the presence or absence of neurovascular unit-derived cytokines. Two morphodynamic parameters, single cell membrane mobility (SCMM) and fractal dimension (Df), were used to analyze the cell contractions and membrane complexity before and after OGD. We found a marginal reduction in cell viability after 2-6h OGD; 24h OGD caused a large reduction in viability and a large increase in the number of apoptotic and dead cells. Application of erythropoietin (EPO), or a combination of EPO and endothelial growth factor (VEGFA1-165) during OGD significantly reduced cell viability; application of Angiopoietin 1 (Ang1) during OGD caused a marginal, insignificant increase in cell viability. Simultaneous application of EPO, VEGFA1-165 and Ang1 significantly increased cell viability during 24h OGD. Twenty minutes and 1h OGD both significantly reduced SCMM compared to pre-OGD values, while no significant difference was seen in SCMM before and after 3h OGD. There was a significant decrease in membrane complexity (Df) at 20min during the OGD that disappeared thereafter. In conclusion, OGD transiently affected cell mobility and shape, which was followed by apoptosis in cultured pericytes. Ang1 may have a potentiality for preventing from the OGD-induced apoptosis. Further studies could clarify the relationship between cell contraction and apoptosis during OGD.